Assessing Als3 Peptide-Binding Cavity and Amyloid-Forming Region Contributions to Candida albicans Invasion of Human Oropharyngeal Epithelial Cells - Oh, Soon-Hwan; Hoyer, Lois L. (Frontiers in Cellular and Infection Microbiology, 2022)
Although it is widely recognized that disruption of ALS3 reduces the invasion of Candida albicans germ tubes into mammalian oral epithelial cells, the mechanism of this interaction was unexplored. C. albicans strains with structurally informed mutations to remove adhesive activity of the peptide-binding cavity (PBC) or aggregative activity mediated by the amyloid-forming region (AFR) were assessed for their ability to invade cultured human oropharyngeal epithelial cells. Initial assays utilized untreated fungal and epithelial cells. Subsequent work used epithelial cells treated with cytochalasin D and C. albicans cells treated with thimerosal to investigate invasion mediated by active penetration of germ tubes and epithelial cell induced endocytosis, respectively. Results demonstrated the importance of the PBC for the invasion process: loss of PBC function resulted in the same reduced-invasion phenotype as a C. albicans strain that did not produce Als3 on its surface. Invasion via active penetration was particularly compromised without PBC function. Loss of AFR function produced a wild-type phenotype in the untreated and thimerosal-treated invasion assays but increased invasion in cytochalasin D-treated epithelial cells. In previous work, reduced AFR-mediated Als3 aggregation increased C. albicans adhesion to cultured epithelial cell monolayers, presumably via increased PBC accessibility for ligand binding. Collectively, results presented here demonstrate that Als3 PBC-mediated adhesion is integral to its invasive function. These new data add to the mechanistic understanding of the role of Als3 in C. albicans invasion into mammalian oral epithelial cells.